Brentuximab vedotin exerts profound antiproliferative and pro‐apoptotic efficacy in CD30‐positive as well as cocultured CD30‐negative germ cell tumour cell lines. Issue 1 (22nd September 2017) - Schönberger, Stefan; van Beekum, Cornelius; Götz, Barbara; Nettersheim, Daniel; Schorle, Hubert; Schneider, Dominik T.; Casati, Anna; Craveiro, Rogerio B.; Calaminus, Gabriele; Dilloo, Dagmar
Abstract: Prognosis in patients suffering from high‐risk, refractory and relapsed germ cell tumours (GCT) often comprising of CD30‐positive embryonal carcinoma (EC) components remains poor. Thus, novel treatment strategies are warranted. The antibody‐drug conjugate (ADC) brentuximab vedotin delivers the potent antimitotic drug monomethyl auristatin E (MMAE) to CD30‐expressing tumour cells. After CD30 binding, internalization and intracellular linker cleavage cytotoxic MMAE can efflux and eradicate neighbouring CD30‐negative cells. To analyse cytotoxicity and a potential bystander effect of brentuximab vedotin in GCT, we established an in vitro coculture model mimicking GCT of heterogeneous CD30 positivity and measured cell viability, proliferation and apoptosis after exposure to brentuximab vedotin and unbound MMAE by MTS‐ and flow cytometry‐based CFSE/Hoechst assay. CD30 expression being assessed by quantitative RT‐PCR and immunohistochemistry was apparent in all EC cell lines with different intensity. Brentuximab vedotin abrogates cell viability of CD30‐positive GCT27 EC line exerting marked time‐dependent antiproliferative and pro‐apoptotic activity. CD30‐negative JAR cultured alone barely responds to brentuximab vedotin, while in coculture with GCT27 brentuximab vedotin induces clear dose‐dependent cytotoxicity. Cellular proliferation and cell death are significantly enhanced in CD30‐negative JAR cocultured with CD30‐positive GCT27 compared to JAR cultured alone in proof of substantial bystander activity of brentuximab vedotin in CD30‐negative GCT. We present first evidence that in an in vitro model mimicking GCT of heterogeneous histology, brentuximab vedotin exerts potent antiproliferative and pro‐apoptotic activity against both CD30‐positive as well as CD30‐negative GCT subsets. Our results strongly support translational efforts to evaluate clinical efficacy of brentuximab vedotin in high‐risk GCT of heterogeneous CD30 positivity.